PEMAKZULAN ANGGOTA MWA UI UNSUR MAHASISWA DARI PERSPEKTIF HUKUM ADMINISTRASI NEGARA - Muhammad Adiguna Bimasakti (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2020)
Law No. 12 of 2012 regarding Higher Education constitute that Higher Education Institution is required to have a Organizing Organization(s) of Higher Education. Universitas Indonesia (UI) as a State University which was regulated in Government Regulation No. 68 of 2013 regarding the Statute of the University of Indonesia (Statute of UI) has a Board of Trustees of the University of Indonesia (MWA UI) which is one of the Organizing Organizations of Higher Education in UI. One element in the MWA UI is the student representative element (MWA UI UM) which is elected once a year by all UI students in a democratic way, and is appointed and discharged based on recommendations from the Academic Senate of the University of Indonesia which is then determined through a Ministerial Decision (Ministry of education). But then the Intra-Campus Student Organizations in UI regulate the impeachment mechanism of MWA UI UM beside the election. Does the impeachment of the MWA UI UM by the Intra-Campus Student Organization of UI have a legal impact on the status of the MWA UI UM membership at the MWA UI? Then how is the mechanism of impeachment / dishonorably discharged for members of the MWA UI UM if the proposal for impeachment comes from Student Organizations in UI? These two questions will be discussed in this article. The method used in this paper is literature study about student organizations of UI, and related laws and regulations.